Study of cryogenic machining for single tip cutting tooll using new cooling system design - Hazwan Aizat, Mohamed Hussin (2008)
In steel machining, high cutting temperature result will reduce the cutting tool life and also reduce the product quality. Conventional cutting fluid used to controlling the high cutting temperature but it is ineffective. Unfortunately, it leads to environment pollution problem. Cryogenic cooling which is an environmental friendly coolant can help rids of conventional fluid pollution problem. Present works are design and fabricate cryogenic coolant system that suit with a conventional lathe machine. Three cylindrical AISI 1045 steel tested up with TNMG TT5100 which is a Chemical Vapor Deposition (CVD) coated tool insert. The result compared with dry machining, machining with soluble oil as coolant and machining with cryogenic coolant; use nitrogen gas as the coolant. Results indicate the benefit of cryogenic cooling in tool life and surface finish. This may be attributed by the reduction of cutting zone temperature. Further, from the result proves that soluble oil failed to improve cutting tool life and product surface finish.